Prof. Protsenko I.Yu. celebrate 80 anniversary - PCSS, Editorial_Team (Physics and Chemistry of Solid State, 2024)
Protsenko Ivan Yukhymovych, Leading researcher of Sumy State University, Doctor of Physical and Mathematical Sciences, Professor, Honored Worker of Science and Technology of Ukraine, member of the editorial board of the scientific journal "Physics and Chemistry of the Solid State"